2004
DOI: 10.1109/tmi.2004.827482
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructions of Chest Phantoms by the D-Bar Method for Electrical Impedance Tomography

Abstract: The problem this paper addresses is how to use the two-dimensional D-bar method for electrical impedance tomography with experimental data collected on finitely many electrodes covering a portion of the boundary of a body. This requires an approximation of the Dirichlet-to-Neumann, or voltage-to-current density map, defined on the entire boundary of the region, from a finite number of matrix elements of the current-to-voltage map. Reconstructions from experimental data collected on a saline filled tank contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
229
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(238 citation statements)
references
References 41 publications
3
229
0
2
Order By: Relevance
“…These two regions appear as one in these images, although other reconstruction algorithms have resolved two lungs under similar test conditions, as did the D-bar algorithm on the experimental tank data in Isaacson et al 2004. The probable cause for this distortion is modeling the chest by a disc. It is well known that such an approximation can cause artifacts; see Adler et al 1996, Gersing et al 1996, Kolehmainen et al 1997, Kolehmainen et al 2005 …”
Section: Resultsmentioning
confidence: 83%
“…These two regions appear as one in these images, although other reconstruction algorithms have resolved two lungs under similar test conditions, as did the D-bar algorithm on the experimental tank data in Isaacson et al 2004. The probable cause for this distortion is modeling the chest by a disc. It is well known that such an approximation can cause artifacts; see Adler et al 1996, Gersing et al 1996, Kolehmainen et al 1997, Kolehmainen et al 2005 …”
Section: Resultsmentioning
confidence: 83%
“…We remark that the method of [33,134] uses, besides CGO solutions, the ∂ method introduced in one dimension by Beals and Coifman [21] and generalized to several dimensions in [1,22,136,196]. The ∂ method has been used in numerical reconstruction procedures in two dimensions in [93,172] among others. The proof of [11] relies also on construction of CGO solutions for the conductivity equation with L ∞ coefficients and the ∂ method.…”
Section: The Calderón Problem In Two Dimensionsmentioning
confidence: 99%
“…Isaacson et al demonstrated in [IMNS04,IMNS06] that the D-bar method performs well on practical data measured from laboratory phantoms and from human subjects. The mandatory regularization step was provided by low-pass filtering in the nonlinear frequency domain.…”
Section: (B)mentioning
confidence: 99%
“…2009(a): The numerical evidence from practical imaging experiments [IMNS04,IMNS06] inspired a rigorous regularization proof of convergence in the form of (1.4), see [KLMS09]. This gave an answer to (iii) and outlined a method for choosing the regularization parameter as the inverse of the nonlinear cutoff frequency.…”
Section: (B)mentioning
confidence: 99%